Решите пожалуйста пределы (математика): 1) lim (x стремится к 9) (x-9)/(√(x)-3) 2) lim (x стремится к 0) (3x)/(√(1+x)- √(1-x)) 3) lim (x стремится к 4) (2-√(x))/(√(6x+1)-5) 4) lim (x стремится к 3) (x^3-27)/(√(3x)-x)

Решите пожалуйста пределы (математика): 1) lim (x стремится к 9) (x-9)/(√(x)-3) 2) lim (x стремится к 0) (3x)/(√(1+x)- √(1-x)) 3) lim (x стремится к 4) (2-√(x))/(√(6x+1)-5) 4) lim (x стремится к 3) (x^3-27)/(√(3x)-x)
Гость
Ответ(ы) на вопрос:
Гость
[latex]\lim_{x \to 9} \frac{x-9}{ \sqrt{x}-3 }= \lim_{x \to 9} \frac{(\sqrt{x}-3)(\sqrt{x}+3)}{ \sqrt{x}-3 }=\lim_{x \to 9} \sqrt{x}+3=6[/latex] [latex]\lim_{x \to 0} \frac{3x}{ \sqrt{1+x}-\sqrt{1-x}}= \lim_{x \to 0} \frac{3x(\sqrt{1+x}+\sqrt{1-x})}{1+x-1+x}=\lim_{x \to 0} \frac{3(\sqrt{1+x}+\sqrt{1-x})}{2} =3[/latex] [latex] \lim_{x \to 4} \frac{2- \sqrt{x}}{ \sqrt{6x+1}-5}= \lim_{x \to 4} \frac{(2- \sqrt{x})(\sqrt{6x+1}+5)}{ 6x-24} = \\ = \lim_{x \to 4} \frac{(2- \sqrt{x})(\sqrt{6x+1}+5)}{ 6(x-4)}= \lim_{x \to 4} \frac{(2- \sqrt{x})(\sqrt{6x+1}+5)}{ 6( \sqrt{x} -2)(\sqrt{x} +2)} = \\ =\lim_{x \to 4} -\frac{(\sqrt{x}-2)(\sqrt{6x+1}+5)}{ 6( \sqrt{x} -2)(\sqrt{x} +2)} = \lim_{x \to 4} -\frac{\sqrt{6x+1}+5}{ 6(\sqrt{x} +2)} = -\frac{10}{24}= -\frac{5}{12}[/latex] [latex] \lim_{x \to 3} \frac{x^3-27}{ \sqrt{3x}-x} = \lim_{x \to 3} \frac{(x-3)(x^2+3x+9)}{ \sqrt{x}( \sqrt{3}-\sqrt{x})} = \\ = \lim_{x \to 3} \frac{( \sqrt{x}-\sqrt{3})( \sqrt{x}+\sqrt{3}))(x^2+3x+9)}{ \sqrt{x}( \sqrt{3}-\sqrt{x})} = \\ = \lim_{x \to 3} -\frac{( \sqrt{3}-\sqrt{x})( \sqrt{x}+\sqrt{3}))(x^2+3x+9)}{ \sqrt{x}( \sqrt{3}-\sqrt{x})} = \\ =\lim_{x \to 3} -\frac{( \sqrt{x}+\sqrt{3})(x^2+3x+9)}{ \sqrt{x}} = -\frac{2 \sqrt{3}*27 }{ \sqrt{3} } =-54 [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы